(untitled) (Palíndromo, 2022)
In each moment, the observed reality is the expression of a gaze contaminated by the observer and by the more or less long time that belongs to the objects; in them, it is condensed an always active process of interference, which often escapes to the real decoding of the works. The painting of the Annunciation (MNMC2528) is precisely one of the cases that requires concentration on detail to rescue a lost integrity. Apparently united by its own iconography (the Archangel Gabriel and the Virgin), the two panels that make it up have reached the 21st century together in one. By analyzing the detail, it was possible to intuit that, in addition to the observable pictorial layer, another truth was hidden, now proven by the conservation and restoration work and the laboratory analyzes carried out. The painting corresponded to two separate panels (and joined at an uncertain time), also hiding the most evident signs (such as the presence of a dog) of another aesthetic culture. The humanist sense of the initial painting became then a more obvious “pamphlet” of the values of the Catholic Reformation (with the attribution to the painter Bernardo Manuel), and like this it reached our days and also the ability to decode the layers of time. A pillar in an interdisciplinary investigative process, the detail assumes itself, in this way, as the great protagonist that leads to the intelligibility of the forms and culture of time.